+0  
 
0
168
1
avatar

e^w+22=21e^-w

Guest Oct 15, 2017
 #1
avatar
0

Solve for w over the real numbers:
e^w + 22 = 21/e^w

21/e^w = 21 e^(-w):
e^w + 22 = 21/e^w

Multiply both sides by e^w:
22 e^w + e^(2 w) = 21

Simplify and substitute x = e^w.
22 e^w + e^(2 w) = 22 e^w + (e^w)^2
 = x^2 + 22 x:
x^2 + 22 x = 21

Add 121 to both sides:
x^2 + 22 x + 121 = 142

Write the left hand side as a square:
(x + 11)^2 = 142

Take the square root of both sides:
x + 11 = sqrt(142) or x + 11 = -sqrt(142)

Subtract 11 from both sides:
x = sqrt(142) - 11 or x + 11 = -sqrt(142)

Substitute back for x = e^w:
e^w = sqrt(142) - 11 or x + 11 = -sqrt(142)

Take the natural logarithm of both sides:
w = log(sqrt(142) - 11) or x + 11 = -sqrt(142)

Subtract 11 from both sides:
w = log(sqrt(142) - 11) or x = -11 - sqrt(142)

Substitute back for x = e^w:
w = log(sqrt(142) - 11) or e^w = -11 - sqrt(142)

e^w = -11 - sqrt(142) has no solution since for all z element R, e^z>0 and -11 - sqrt(142)<0:
w = log(sqrt(142) - 11)    Log here is "natural log(ln)"

Guest Oct 15, 2017
edited by Guest  Oct 15, 2017

14 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.